Facts about Minerals - R. Elaine Turner (EDIS)
FCS8809, a 4-page fact sheet by R. Elaine Turner, goes over the different types of minerals, their functions, the foods they can be obtained from, and the pros and cons of supplementation. Published by the UF Department of Family, Youth and Community Sciences, December 2006.